Bath mat drowning prevention project. (7th October 2012) - Campbell, S; Robinson, C
Abstract : Background: Water presents a potentially life threatening hazard for young children in and around the home and in the wider community. Preschool children have one of the highest drowning rates of all New Zealanders with a lack of appropriate adult supervision being the primary cause of drowning incidents. In the 5 years (2007–2011) 47 children under the age of 5 years have drowned. 53% of these drownings occurred in the home environment, predominantly a home swimming pool or the bath. Water Safety New Zealand has partnered with Plunket in developing a campaign to create greater awareness and educate parents and caregivers on the importance of water safety for young children. Aims: Reduce water related injuries and drowning in children under 5 in New Zealand and increase awareness for the need for constant supervision of these children in and around water. Method: Delivery of a non-slip bath/shower mat with the bilingual message, ALWAYS SUPERVISE CHILDREN AROUND WATER—ALWAYS—' Tiakina ngā tamariki ki te taha wai i ngā wā katoa ', to each family at the 5 month check with the Plunket Nurse combined with a discussion about water safety. Follow up discussion takes place at the next contact between nurse and family. Results: Over 100 000 mats delivered and drowning prevention conversations initiated with whanau. Evaluation has shown the campaign is effective. The bath mat is widely used, communicates a vital water safety message directly to new parents and is instrumental in positive attitude change.